Performance and emission characteristics of green diesel blends containing diethyl-succinate and 1-octanol. (10th September 2017) - Phoon, L.Y.; Mustaffa, A.A.; Hashim, H.; Mat, R.; Manan, Z.A.; Yunus, N.A.
Abstract: Further enhance the oxygen content (OC) of the conventional B5 palm oil biodiesel is the key to attain greener emissions in future. Diethyl succinate (DES) and 1-octanol (OCT) is designed to blend with B5 to address this issue. In this study, the optimum binary and ternary blends (with higher OC) of B5 with DES and/or OCT are obtained using a computer-aided decomposition-based optimization. The predicted fuel properties (density, kinematic viscosity, higher heating value (HHV) and flash point) and engine performances including fuel efficiency: brake thermal efficiency (BTE) and brake specific fuel consumption (BSFC) and emissions of nitrogen oxides (NOx ), carbon monoxide (CO) and un-burnt hydrocarbon (UHC) of the optimum blends are evaluated experimentally. 2-ethylhexyl nitrate (2EHN) is used to enhance the cetane number of the optimum blends to improve their combustion quality. Ternary blend of B5 with DES and OCT could attain higher OC than binary blends with satisfied target fuel properties. The predicted fuel properties such as density, HHV and flash point are well agreed with experimental value except kinematic viscosity. The designed optimum blends generally have greener emissions than B5 while having similar fuel efficiency with B5. T1A ternary blend (B5 = 70.0%; OCT = 24.1%; DES = 5.9% with 0.20% 2EHN) appear as the most promising green diesel blend owning to its greener emissions (NOx, CO and UHC) and similar fuel efficiency with B5.